Extended Thermodynamic Approach for Non-Equilibrium Gas Flow (Communications in Computational Physics, 2013)
Gases in microfluidic structures or devices are often in a non-equilibriumstate. The conventional thermodynamic models for fluids and heat transfer breakdown and the Navier-Stokes-Fourier equations are no longer accurate or valid. Inthis paper, the extended thermodynamic approach is employed to study the rarefiedgas flow in microstructures, including the heat transfer between a parallel channel andpressure-driven Poiseuille flows through a parallel microchannel and circular microtube. The gas flow characteristics are studied and it is shown that the heat transfer inthe non-equilibrium state no longer obeys the Fourier gradient transport law. In addition, the bimodal distribution of streamwise and spanwise velocity and temperaturethrough a long circular microtube is captured for the first time.